2022
DOI: 10.7554/elife.75526
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of protein complex partners as a compensatory mechanism in aneuploid tumors

Abstract: Aneuploidy, a state of chromosome imbalance, is a hallmark of human tumors, but its role in cancer still remains to be fully elucidated. To understand the consequences of whole-chromosome-level aneuploidies on the proteome, we integrated aneuploidy, transcriptomic and proteomic data from hundreds of TCGA/CPTAC tumor samples. We found a surprisingly large number of expression changes happened on other, non-aneuploid chromosomes. Moreover, we identified an association between those changes and co-complex members… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…This trend is exemplified by ribosomal complex proteins ( Stingele et al 2012 ; Dephoure et al 2014 ), which showed highly significant dosage compensation. A recent study showed that protein complex subunits located on nonaneuploid chromosomes tend to co-regulate with their co-complex partners on aneuploid chromosomes in human tumor samples ( Senger et al 2022 ). We discovered that protein complex subunits were also buffered upon chromosome arm loss.…”
Section: Discussionmentioning
confidence: 99%
“…This trend is exemplified by ribosomal complex proteins ( Stingele et al 2012 ; Dephoure et al 2014 ), which showed highly significant dosage compensation. A recent study showed that protein complex subunits located on nonaneuploid chromosomes tend to co-regulate with their co-complex partners on aneuploid chromosomes in human tumor samples ( Senger et al 2022 ). We discovered that protein complex subunits were also buffered upon chromosome arm loss.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly protein level compensation. RNA-level compensation in certain tumor types RNA-level compensation for non-complex genes RNA-protein correlation informs protein-level regulation [43] DNA-RNA correlation informs RNAlevel regulation [43] Protein complexes Genes that code for protein complexes Accelerated breakdown of nonassembled subunits [78,79] Protein degradation by ubiquitinproteasome system [78,80,81] Acetylation of the N-terminal amino acid by N-acetyltransferases (NAT) [79,81,82] Co-deregulation of protein complex partners [83] (Continues) addition, when combined with criteria such as the formation of protein complexes, only 70% of NED proteins form those complexes. Therefore, a precise definition of gene dosage compensation is difficult to achieve, especially because the threshold of the gene expression scaling as a function of copy number could be different for each gene and probably also depends on the cellular context.…”
Section: Bimodal Distribution Of the Strength Of Association By Spear...mentioning
confidence: 99%
“…43 A characterization of the transcriptome and proteome in aneuploid human cancers showed that 47%-63% of the genes located in aneuploid chromosomes evidence changes in expression at the transcriptome level, in contrast to only 24%-33% at the proteome level. 83 However, the degree of expression changes induced by aneuploidy varies depending on multiple factors, among them the cellular environment. 16 For instance, Senger et al found that genes on other chromosomes show a surprising degree of differential expression.…”
Section: Compensation Mechanisms At the Rna Levelmentioning
confidence: 99%
See 2 more Smart Citations